REVIEW ON THE GREEN SYNTHESIS OF MAGNETIC IRON OXIDE NANOPARTICLES: METHODS, MECHANISMS, AND APPLICATIONS - Vijay Krishanan; Devasena, B; Nafisa Farheen; Shobana, S; Geetha, C (The Bioscan, 2025)
The synthesis of magnetic iron oxide nanoparticles has gained significant interest due to their wide-ranging applications in biomedical and environmental fields. While traditional physical and chemical methods pose ecological and toxicity concerns, green synthesis using plant extracts offers an eco-friendly and cost-effective alternative. This review comprehensively discusses chemical, microbial, and especially plant-mediated synthesis routes for iron oxide nanoparticles. Characterization, mechanisms of formation, and potential applications in catalysis, drug delivery, and wastewater treatment are also highlighted.